Effect of Excessive Monosodium Glutamate (MSG) Consumption on Brain Function and Structure: A Systematic Review in Animal Models - Annida Nurhidayah; Anton Budhi Darmawan (Indonesian Journal of Global Health Research, 2025)
Monosodium glutamate (MSG) is widely used as a flavor enhancer, but excessive consumption has been linked to neurotoxicity. Poor dietary intake affects neurotransmitter balance, oxidative stress levels, and long-term neuronal health. Objective: To evaluate the effects of excessive MSG consumption on brain function and structure using animal models. Method: A systematic review was conducted using PubMed, Google Scholar, and ResearchGate (2014–2024). From 1,692 initially identified articles, 8 were selected using the PICO method, focusing on MSG exposure, neurotoxicity, and structural or functional brain changes in animal models. Results: Studies indicate that MSG exposure contributes to neurotransmitter imbalances, increased oxidative stress, and neuronal degeneration, leading to cognitive impairment and behavioral alterations. Additionally, elevated tau phosphorylation and neuroinflammation were observed, potentially increasing the risk of neurodegenerative conditions such as Alzheimer’s disease. The route of administration (oral vs. intraperitoneal) and duration of exposure influenced the severity of effects. Conclusion: Excessive MSG consumption negatively affects brain function and structure through mechanisms such as excitotoxicity, oxidative stress, and neuroinflammation. Further research is needed to standardize dosage thresholds, explore protective interventions, and assess long-term effects in mammalian models.